Konsep Hard Skill, Soft Skill Dan Spiritual Skill Pustakawan Menghadapi Era Library 3.0 - Rotmianto, Mohamad (STAIN Ponorogo, 2015)
InÂ thisÂ presentÂ time,Â librarianÂ mustÂ knowÂ wellÂ about information technology orÂ it also called have aÂ literacy ofÂ information technology.Â BecauseÂ theyÂ (librarian)Â willÂ faceÂ theÂ âexplosionÂ of informationâ, as well as a newÂ library user named âNet Generationâ who wants all information to be presented more accurate, quicker and interactively, as the demands of Library 3.0. Mastery three skills: hard skillÂ (IQ)Â andÂ softÂ skillÂ (EQÂ Â )Â combinedÂ withÂ spiritualÂ skillÂ (SQ)Â is requiredÂ toÂ succeedÂ to be a Librarian 3.0,Â so not only qualifedÂ inÂ the feld of technology, but more than that librarians also have a humanism side that is based on religious principles.